Evolving government information processes for service delivery: Identifying types & impact - Roel Heijlen; Joep Crompvoets; Geert Bouckaert; Maxim Chantillon (Administrative Sciences, 2018)
The fulfilment of government objectives is dependent on information. Traditionally, this information originates from a classic process of input, (processing) activities, and output. However, in light of increased intergovernmental data sharing, the movement towards open data and opportunities concerning big data, traditional government information processes are evolving. This article aims to bring insight into these evolutions by creating a typology. Based on the typology, the paper further reflects on the impact these evolutions have on the processes and creation, delivery and improvement of public service.
Keywords: 350; government information; process evolutions; service delivery; typology; intergovernmental data sharing; big data; open data